Means of egress in hospital wards in Perak, Malaysia / Muhammad Amir Ezzat Nasaruddin and Adnin Syaza Jaafar - Nasaruddin, Muhammad Amir Ezzat; Jaafar, Adnin Syaza (2020)
Hospital building is one of the building that has a massive chance to involve in a fire incident. Efficient means of egress need to be implemented because fire incident leads to lose of lives for those who trapped inside the hospital. This paper is intended to establish an effective means of escape in hospital wards. The objectives were to (1) to assess current condition of implemented means of egress in hospital wards, (2) to identify the level of staffs and visitors' awareness towards means of egress in hospital wards and (3) to suggest the effective ways to enhance the effectiveness of means of escape in hospital wards. Three hospitals in Perak that was built before the existence of Uniform Building By-Laws 1984 (UBBL 1984) were chosen as cases study. Both quantitative and qualitative method were used in this research where questionnaires were distributed to 90 people in those three hospitals and observation were made for the assessment of the condition of implemented means of egress. All data collected were analysed using descriptive statistic. Based on the observation, all three hospitals are implementing the means of escape in accordance with the standard guidelines. The results found that the awareness upon means of egress is at a satisfactory level. However, some of the respondents still lacking of awareness in some criteria. Several ways to enhance the means of egress were also acquired through the questionnaire distributed such as displaying more fire evacuation plan and adding notes regarding the usage of fire doors in every ward.